Promoting Alaska native wellbeing and suicide prevention in rural schools: a virtual learning circle approach - Evans, Elizabeth; White, Lauren; Schmidt, Tara; Zhong, Angel; McEachern, Diane; Moto, Roberta; Garnie, Josie; Issac, Leanna; Chaliak, Jim; Wexler, Lisa (Frontiers in Education, 2026)
IntroductionSuicide is a leading cause of death among youth in the United States, with particularly high rates among American Indian and Alaska Native (AIAN) youth in rural areas. Schools can serve as critical settings for suicide prevention by fostering mental health and caring environments. This can be done by teaching and supporting staff and community adults to work together to reduce mental health risks and enhance student wellbeing. The Promoting Community Conversations about Research to End Suicide (PC CARES) program uses a series of community-based workshops to share research-based strategies and promote every day, culturally grounded actions that support mental wellness and prevent suicide. This study explores how participants engaged with PC CARES and describes their perceptions of research content, and ideas for applying the information in school settings.MethodsUsing qualitative data from virtual PC CARES sessions delivered with three rural Alaskan school districts from 2020 to 2022, this study shows how participants (school staff, administrators, and behavioral health professionals) who attended seven online facilitated sessions made sense of and used learning. Notes and written responses were deductively analyzed for themes.ResultsAcross 28 sessions (56 h) over two academic years, participants discussed integrating Alaska Native Elders into school activities, modeling healthy behaviors, creating space for youth expressions, and incorporating cultural identity into programming. They emphasized the power of small acts of kindness and trusted relationships as protective factors for youth. Institutional challenges included inconsistent policies and limited resources.DiscussionParticipants engaged actively with the learning materials, considering how to adapt the information to their own school and community contexts. These findings suggest that PC CARES can serve as a strengths-based, culturally relevant platform for school-based suicide prevention, while highlighting the need for institutional support to sustain such efforts. Future research should explore long-term sustainability and student-level outcomes.